Capitalisme cognitif et modèles urbains en mutation - Raphaël Besson (Territoire en Mouvement)
In the recent capitalism mutations, knowledge tends to replace natural resources and physical work as economic growth tools. This deeply transforms modern cities. Progressively, contemporary cities fit their productive, spatial and organizational structures to new economy demands. One of the most evident sign of these mutations lies in the multiplication of projects such as « technological districts », « creative » or « cultural clusters », « design districts » or even « cyberdistricts ».The working hypothesis we will defend in this article emphasizes the fact that these projects are all developed on a same model, the model of « Cognitive Urban Systems » (CUS). Those CUS emerge at the core of the cities as the consequence of strong public policies of socio-economic and urban revitalization, on emblematic fordist areas of approximately 200 acres. Their purpose is to create favourable spaces for the production and valorization of innovations. This is made possible by the concentration of formal and informal institutions which interact between them as well as with the economic, spatial and sociocultural fabric of the cities through intense and varied proximity connexions, the aim of which is to generate a systemic and opened dynamic of innovation in the hybrid and technologic sectors.To illustrate this thesis, we will put emphasis on a comparative analysis, currently in progress in four CUS implemented in three cities : Barcelona (22@barcelona), Bueno Aires (Distrito Tecnológico ; Distrito de Diseño) et Grenoble (GIANT / Presqu’île).